Is determinism more favorable than indeterminism for the causal Markov condition? - Drouet, Isabelle (Philosophy of Science, 2009)
The present text comments on Steel 2005, in which the author claims to extend from the deterministic to the general case, the result according to which the causal Markov condition is satisfied by systems with jointly independent exogenous variables. I show that Steels claim cannot be accepted unless one is prepared to abandon standard causal modeling terminology. Correlatively, I argue that the most fruitful aspect of Steel 2005 consists in a realist conception of error terms, and I show how this conception sheds new light on the relationship between determinism and the causal Markov condition.